â€œErongâ€ as Supplementary Learning Materials for Tourism Geography of Toraja Tribe in South Sulawesi, Indonesia - Suni, Muhadjir; Ridwan, Masri (Richtmann Publishing, 2019)
'Erong' in Toraja Tribe is a funeral tradition which is potentially used as a learning source for Tourism Geography. The research aimed at discovering the use of ‘erong’ in funeral tradition of Toraja. The concerns of this research were the history of 'erong’, its the development process, and the optimalization of 'erong' as supplementary learning materials on the topic of potential attraction on the Tourism Geography course in Tourism Polytechnic of Makassar. This ethnographic study employed observation and in-depth interview in collecting the data. The collected data applied was based on their category and chronology then simultaneously checked and coded. The data verification strategy used triangulation, member checking, and audit trial. This research revealed the history underlying the tradition of ‘erong’ including the belief in Aluk Sanda Pitunna (Rule 7777) which was originated from the teachings of the ancestors (Aluk Todolo). ‘Erong’ as Austronesian culture came through the transformation into Pata'ne. Nowadays the uniqueness of Toraja's culture makes it popular as destination for both local and international tourists. In optimizing the integration of this tradition into curriculum of Tourism Geography within the scope of Tourism Polytechnic of Makassar, the result of this research will become supplementary textbook. Further study is recommended to conduct in-depth research on the potential of other local tourism destinations in Toraja such as Rambu Solo ceremony (funeral), Rambu Tuka (thanksgiving), traditional house Tongkonan, and Passiliran (baby grave).